Effectiveness of Finger Hold Technique and Guided Imagery on Reducing Primary Dysmenorrhoea Pain Intensity - Intan Putri Utami; Maudy Lila Kartika; Dessy Salmayanti Putri (Oksitosin : Jurnal Ilmiah Kebidanan, 2025)
An important phase of adolescent growth is puberty. It is identified in women with the onset of menstruation. Dysmenorrhoea is one of the discomforts that some women experience during menstruation. Among the non-pharmacological methods for pain management are Guided Imagery and finger holding. The aim of this study was to ascertain how well the Finger Holding and Guided Imagery approaches work to reduce the severity of primary dysmenorrhoea discomfort. Approach. Randomised Pretest-Posttest Control Group Design was used in this study as the real experimental design, and random sample methodology was used as the sampling method. 34 respondents formed the sample size of the study, with 17 respondents in each of the intervention and control groups. The data analysis used to assess the difference in levels used the Wilcoxon test. To assess differences in differences using the Mann Whitney test. According to the data, the pain scale had dropped to 5.117 before the intervention, falling into the moderate discomfort category. 3.058 was the value in the mild group after the intervention. Additional examination of the decrease in pain scale after finger holding and Guided Imagery showed a difference of 0.000 in the decrease in pain scale, with a p value of 0.000. As a result, the use of finger holding and guided imagery had an impact on the decrease of dysmenorrhoea pain scale.